2016
DOI: 10.1108/jfp-06-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

A place to call home: perspectives on offender community reintegration

Abstract: Purpose The purpose of this paper is to explore offenders’ experiences of community reintegration facilitated by a supported housing scheme. Design/methodology/approach Data were derived from five semi-structured interviews with prolific offenders who were participating in a UK “north west housing association” scheme; a community reintegration programme for offenders released from prison. Findings Thematic analysis demonstrated four predominant themes, these were: “the decision to change”, “self-fulfilment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Six studies reported other social and mental wellbeing outcomes [ 41 , 44 , 49 , 52 , 54 , 59 , 61 ]. One included a control group and reported a positive effect direction on feelings of autonomy [ 59 ], however the data were qualitative and like the remaining studies, used self-reported outcomes [ 41 , 44 , 49 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported other social and mental wellbeing outcomes [ 41 , 44 , 49 , 52 , 54 , 59 , 61 ]. One included a control group and reported a positive effect direction on feelings of autonomy [ 59 ], however the data were qualitative and like the remaining studies, used self-reported outcomes [ 41 , 44 , 49 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported other social and mental wellbeing outcomes [ 41 , 44 , 49 , 52 , 54 , 59 , 61 ]. One included a control group and reported a positive effect direction on feelings of autonomy [ 59 ], however the data were qualitative and like the remaining studies, used self-reported outcomes [ 41 , 44 , 49 , 54 ]. Other outcomes included community integration, sense of autonomy or control over one’s life, stigma, cultural connectedness, and a number of mental health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…One of the few (Coffey, 2012) focussed on the challenges associated with creating a "non-deviant" identity in the outside world, a task made more difficult by continued supervision and monitoring. Other studies using a sample of the prison population (Tarpey & Friend, 2016) yielded relevant findings, identifying the importance of self-fulfilment, suitable support systems, and the decision to change.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that post-release, women have greater problems securing housing than their male counterparts (Baldry et al 2006). Yet having a place to call home is imperative for successful re-entry, as it enables women to regain independence, privacy, and to exert autonomy (O'Brien 2001;Opsal 2015;Heidemann et al 2016;Tarpey and Friend 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there is a strong correlation between poor accommodation and negative outcomes (O'Brien and Leem 2007;Severance 2004;Tarpey and Friend 2016). Research by Baldry et al (2006), for example, found that women who have unstable or unsuitable accommodation are more likely to return to prison.…”
Section: Introductionmentioning
confidence: 99%